Competitive Engineering - A Handbook for Systems Engineering, Requirements Engineering, and Software Engineering Using Planguage - Gilb, Tom (Elsevier, 2005)
This book documents Tom Gilb's unique, ground-breaking approach to communicating management objectives and systems engineering requirements, clearly and unambiguously. Competitive Engineering is a revelation for anyone involved in management and risk control. Already used by thousands of project managers and systems engineers around the world, this is a handbook for initiating, controlling and delivering complex projects on time and within budget. Competitive Engineering copes explicitly with the rapidly changing environment that is a reality for most of us today. Elegant, comprehensive and accessible, the Competitive Engineering methodology provides a practical set of tools and techniques that enable readers to effectively design, manage and deliver results in any complex organization in; Engineering, industry, systems engineering, software, IT, the service sector and beyond.